Pre-contrast CT calcium score correlation with significant risk factors for coronary artery disease. Issue 1 (March 2023) - Alshalaggi, Salah; Osman, Hamid; Elsamani, Mohammed; Alshammari, Qurain; Abdullah, Ibtisam; Almeshari, Meshari; Alkhybari, Essam; Abanomy, Ahmad; Khandaker, Mayeen Uddin; Alzamil, Yasser
Abstract: Computed Tomography (CT) scan is one of the most widely used methods for evaluating the pre-contrast CT calcium scoring. This study aims to assess the correlation of pre-contrast CT calcium scoring with major risk factors for coronary artery disease (CAD). A descriptive study was conducted from Oct 2021 to Jan 2022 and included 109 patients. The mean age of the patients was 54.5 ± 14.1 (range 40–79) years old. The spreadsheet was used to gather the data via Picture Archive and Communication System (PACS) from the radiology department of King Salman Specialist Hospital, Hail (KSSHH). The study showed the percentage of male and female patients were 41.0% and 59.0%, respectively. More than zero calcium score among males was found to be 67.0%, whereas among females, it was at least 50.0%. The male group of 60–79 years old was found to be the most effected age group with more than zero calcium, while the female age group of 70–79 years showed the same zero calcium score. The percentage of calcium prevalence (score >0) in coronary arteries is affected by a number of risk factors. Coronary artery calcium (CAC) has emerged as a consistent means for assessing the risk of primary cardiovascular outcomes, especially for asymptomatic people. This study showed that the patient group with more than one risk factor for coronary heart disease had no evidence of calcium scoring. Study recommends to enlarge sample size in the coming future studies and to perform calcium scoring using CT scan before computed tomography angiofraphy (CTA).